Model-Model Penelitian Kualitatif - Rachel Humayra; Meyniar Albina (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The research aims to examine qualitative research models used across various scientific disciplines. The method applied in this study is a qualitative approach using a literature review. Data sources were gathered from books, journals, and scientific articles. The findings indicate six main qualitative research models: ethnography, case study, document study, natural observation, grounded theory, and phenomenology. Each model is unique in approach and application depending on the research objective. This study concludes that qualitative methods offer a more in-depth and flexible approach to understanding social and cultural phenomena. This paper serves as a reference for academics and practitioners in choosing the appropriate research model.